Applications and effects of ultrasound assisted emulsification in the production of food emulsions: A review. (April 2021) - Zhou, Lei; Zhang, Jian; Xing, Lujuan; Zhang, Wangang
Abstract: Background: The number of people who are aware of consuming healthy and natural foods are consistently increasing. Natural emulsifier-stabilized emulsions have attracted widespread attention in food industry. Ultrasound has a potentially wide range of applications in the preparation of food emulsions. Scope and approach: This review briefly discussed the effects of ultrasound-assisted emulsification (UE) on emulsion formation along with introducing the different emulsifier stabilized emulsions. In special, the effects of UE on the emulsion properties such as viscosity, emulsifying properties, droplet size, zeta potential, emulsifier properties and oil phase properties have been summarized. Finally, the advantages and disadvantages of current studies on UE in food system were also discussed. Key findings and conclusions: The review demonstrated that the process of UE may not be a simple process of breaking up droplets, but may be a more complicated process. UE can be used to prepare many emulsifier stabilized food emulsions such as protein, polysaccharide, protein-polysaccharide and protein-polysaccharide-surfactant. Proper UE treatment could improve the rheological properties and emulsifying properties, reduce the emulsion droplet size as well as increase the absolute zeta potential of emulsions. UE was shown to be a good method to unfold proteins and form good emulsions. However, the studies on sonication induced emulsifier properties were still limited. High-intensity ultrasound had no significant influence on the oil oxidation and oil profiles, whereas increased the anti-oxidative ability of some emulsions. Beside the large-scale ultrasonic devices should be developed, the effects of UE on emulsifier and oil phase during and after sonication should be further studied in the future. Highlight: Ultrasound emulsification (UE) treatment could reduce the droplet size of emulsions. UE treatment could increase the absolute zeta potential of emulsions. UE treatment could improve the rheological and emulsifying properties of emulsions. The formation mechanism of UE on the food emulsion might be complicated. The studies on UE induced emulsifier properties are still limited.